2006
DOI: 10.1002/humu.9417
|View full text |Cite
|
Sign up to set email alerts
|

Distinct patterns of germ-line deletions inMLH1 andMSH2: the implication of Alu repetitive element in the genetic etiology of Lynch syndrome (HNPCC)

Abstract: A relatively high frequency of germ-line genomic rearrangements in MLH1 and MSH2 has been reported among Lynch Syndrome (HNPCC) patients from different ethnic populations. To investigate the underlying molecular mechanisms, we characterized the DNA breakpoints of 11 germ-line deletions, six for MLH1 and five for MSH2. Distinct deletion patterns were found for the two genes. The five cases of MSH2 deletions result exclusively from intragenic unequal recombination mediated by repetitive Alu sequences. In contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 27 publications
1
38
0
1
Order By: Relevance
“…18 In contrast, MLH1 genomic deletions have been found to involve not only Alu repeats, but also nonhomologous sequences. 2,3,9,20,21 As expected, exonic MSH2 and MLH1 duplications, the reciprocal genomic alterations of deletions resulting from unequal crossingover, have also been detected in HNPCC families, but at a much lower frequency. We reported, using QMPSF, the first case of a MSH2 duplication involving exons 9 -10 that was confirmed by long-range PCR 5 and we subsequently detected another MSH2 duplication involving exons 7 -8.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…18 In contrast, MLH1 genomic deletions have been found to involve not only Alu repeats, but also nonhomologous sequences. 2,3,9,20,21 As expected, exonic MSH2 and MLH1 duplications, the reciprocal genomic alterations of deletions resulting from unequal crossingover, have also been detected in HNPCC families, but at a much lower frequency. We reported, using QMPSF, the first case of a MSH2 duplication involving exons 9 -10 that was confirmed by long-range PCR 5 and we subsequently detected another MSH2 duplication involving exons 7 -8.…”
Section: Introductionsupporting
confidence: 54%
“…2 -24 We previously estimated that genomic deletions of MSH2 and MLH1 respectively, account for approximately 10 and 4% of HNPCC families fulfilling Amsterdam criteria. 6,13 All the MSH2 genomic deletions detected so far have been shown to result from unequal Alu-mediated recombinations 6,8,11,12,18,20 and we found that the density of Alu S repeats within the MSH2 5 0 region was remarkably high, compared with other human genes. 18 In contrast, MLH1 genomic deletions have been found to involve not only Alu repeats, but also nonhomologous sequences.…”
Section: Introductionmentioning
confidence: 54%
“…Indeed, there are numerous reports of disease-causing deletions resulting from recombination between Alu elements (Batzer and Deininger, 2002;Nishimura et al, 2005;Casarin et al, 2006;Has et al, 2006;Kozak et al, 2006;Li et al, 2006;Matejas et al, 2006;Nissen et al, 2006;Sen et al, 2006;Shabbeer et al, 2006;Uddin et al, 2006;Xie et al, 2006;Zhang et al, 2006). If a large proportion of Alu elements indeed fosters euchromatic domains as suggested by the aforementioned study (Willoughby et al, 2000), then flanking sequences may also be destabilized.…”
Section: Non-random Repeat Distributions Via Natural Selectionmentioning
confidence: 94%
“…Previous reports document two large germline MLH1 deletions in which the break points mapped to an L1 element and nonrepetitive DNA sequence, respectively. 12 Viel et al, reported a 2454-bp deletion in MLH1, likely because of the recombination between two L1 elements in intron 2 and intron 3. 13 Interestingly, this allele with the MLH1 deletion was also characterized by a complex mutation delCCinsACATAGTA, which gave rise to a palindromic sequence in the proximity of the fusion site.…”
Section: Discussionmentioning
confidence: 99%